Development of an activity-based probe for amyloid β-hydrolyzing antibodies. Issue 9 (1st May 2016) - Taguchi, Hiroaki; Fujita, Yoshio; Tsuda, Yuko
Graphical abstract: Abstract: We report developing an activity-based probe containing an amyloid β peptide (Aβ) 17–27 and an electrophilic phosphonate diester at the C-terminus. A probe containing an electrophilic moiety is able to react with the nucleophiles on an antibody or an antibody with proteinase activity. The probe reacted with an Aβ specific monoclonal antibody and formed a covalent complex. The covalent binding also occurred specifically when the probe reacted with serum containing anti-Aβ antibodies. These results suggest that the probe would serve as a powerful tool to isolate Aβ specific antibodies that are capable of Aβ hydrolysis activity.